Prediction of knee extensor and flexor isokinetic strength in young male soccer players - Kellis, S.; Kellis, E.; Manou, V.; Gerodimos, V. (Journal of Orthopaedic & Sports Physical Therapy, 2000)
STUDY DESIGN: Single group, cross-sectional study. OBJECTIVES: To measure various anthropometric and demographic variables in young male soccer players and to use these measurements to develop equations with which to predict the isokinetic, concentric, and eccentric moment of force. BACKGROUND: The development of equations that can predict isokinetic muscle strength from commonly measured subject characteristics can assist in the effective design of training and rehabilitation programs for athletic children. METHODS AND MEASURES: One hundred thirteen male soccer players (13.50 +/- 2.21 years of age) performed eccentric and concentric maximum efforts of the knee extensors and flexors at 60, 120, and 180 degrees/second. Stepwise regression tests were used to develop predictive equations using combinations of age, height, body mass, sexual maturation (Tanner) stage, percentage of body fat, and hours spent training per week. RESULTS: The results indicated a significant relationship of concentric and eccentric isokinetic strength for both knee extensors and flexors with 73-93% of the variance explained by using combinations of age, body mass, percentage of body fat, and hours training per week. Body mass and age were the main predictor variables under concentric conditions, whereas chronological age was not included in the models under eccentric conditions. CONCLUSIONS: The relation between isokinetic moment and multiple anthropometric and demographic variables depends on the type of muscle action examined. The results suggest that the equations we developed can be used to predict the isokinetic moment in trained, young soccer players. A cross-validation analysis is required to confirm the accuracy and the suitability of the equations developed in our study.